An Analysis of the Cyclical Narrative Pattern in the Book of Judges - XIANG, Haonan (Journal of Research for Christianity in China (JRCC), 2025)
The Book of Judges is a significant chapter among the historical books of the Old Testament in the Bible. It chronicles the major historical events of the Israelites after their entry into the land of Canaan, spanning the period from Joshua's death to the birth of Samuel, the last judge of Israel. From a narrative perspective, Judges employs a distinctive cyclical pattern. The story of each judge can be broadly summarized as a five-part sequence: “apostasy—punishment—repentance—deliverance—fulfillment,” a pattern that repeats seven times throughout the book. This paper, grounded in an in-depth study of the Book of Judges, endeavors to comprehensively and meticulously examine and summarize its cyclical narrative pattern. It aims to identify its inherent characteristics and analyze the profound significance embedded within.